Development and performance evaluation of battery assisted weeder for paddy crop - Borkar, Narayan Totaram; Nayak, Amaresh Kumar; Sivashankari, M (ORYZA-An International Journal of Rice, 2026)
A battery-assisted single-row weeder was developed and evaluated in comparison with a conventional manually operated cono-weeder for wetland rice cultivation. The developed weeder consists of a frame, DC motor, battery pack, transmission system, controller, cutting unit, handle, and support wheel. Power from the battery-operated DC motor is transmitted to the cutting unit through a chain-sprocket mechanism, while a controller regulates uniform power supply and operational speed. Three cutting units-J-type, L-type, and cage wheel type-were evaluated at a row spacing of 20 cm. Performance parameters such as field capacity, field efficiency, weeding efficiency, plant damage, labour requirement, cost economics, and energy consumption were assessed. Results indicated that the battery-assisted weeder achieved an actual field capacity of 0.03 ha h-1, which was more than twice that of the manually operated cono-weeder. It also recorded higher field efficiency (85%), lower plant damage (1.94%), and reduced labour requirement (34 man-h ha-1). The cost of operation was Rs. 4108 ha-1, which was lower than that of the cono-weeder (Rs. 4712 ha-1). Overall, the battery-assisted weeder significantly reduced labour drudgery and operational time while lowering weeding costs, indicating its potential as an efficient mechanized weeding option for small and medium-scale rice farmers.